ОСОБЛИВОСТІ РОБОТИ АВТОНОМНИХ ЗАРЯДНИХ СТАНЦІЙ ЕЛЕКТРОМОБІЛІВ З ВИКОРИСТАННЯМ ВІТРОЕЛЕКТРИЧНИХ УСТАНОВОК ТА БУФЕРНИХ АКУМУЛЯТОРІВ ЕНЕРГІЇ - Павлов , В.Б.; Кудря , С.О.; Будько , В.І.; Кириленко , В.М.; Іванчук , В.Ю. (Інститут електродинаміки НАН України, Київ, 2019)
A mathematical description of the operation of an autonomous charging station of electric vehicles with the use of wind turbines is proposed. The energy intensity of the buffer energy accumulator is substantiated when implementing autonomous charging stations of electric vehicles with the use of wind power plants as electric power generators. The features of providing electric energy of the charging station on the basis of real data of wind speed are considered. The installed energy buffer battery is required for the guaranteed charge of electric vehicles. References 12, figures 5.